Dynamic learning spaces—dynamic pedagogy. Students’ voices from a master’s program focusing on student active learning in a cross-institution two-campus organization - De Caro-Barek, Veruska; Lysne, Dag Atle; Støckert, Robin; Solbjørg, Ole Kristen; Røren, Kari Anne Flem (Frontiers in Education, 2023)
This article presents the results from an exploratory case study within the frame of an ongoing larger research project closely linked to a cross‐campus and cross‐institution master’s degree program at the Norwegian University of Science and Technology (NTNU). The master’s program is a collaboration between NTNU and the University of Oslo (UiO) and is co-located at both campuses through one shared hybrid, physical and virtual, learning space called the Portal. The genesis of the Portal is informed by Radcliffe’s Pedagogy‐Space‐Technology framework for the design and evaluation of learning spaces. The scope of our research focuses on the “user experiences”, particularly on how students experience their learning space as an arena for student active learning and collaborations in a cross-campus (and cross-institution) organization. In an increasingly digitalized world, successfully designing cross‐campus and multi‐campus hybrid and fully digital learning environments to sustain learners’ education and promote the development of critical skills to meet future work-life challenges and possible new crises has become pivotal to ensuring the survival of Higher Educational Institutions. It is therefore increasingly important to include students’ experiences and feedback to help develop and define standards and frameworks that can guide educators and other stakeholders in their work. With this article, we hope bringing in newer insight and, hopefully, a fresh point of view.